Histomorphological and biochemical studies of the Pancreatic B-Cells, kidney and liver in streptozotocin-induced diabetic Wistar rats treated with methanolic extra of Hibiscus Sabdariffa(Linn) - Adeyemi, David Olawale (Obafemi Awolowo University, 2019)
xxvii,174 pages